2019
DOI: 10.2344/anpr-66-01-07
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Rocuronium-Induced Anaphylaxis/Anaphylactic Shock Successfully Treated With Sugammadex

Abstract: While anaphylaxis can occur at any time during general anesthesia, 90% of cases occur at induction of anesthesia. As several drugs are administered simultaneously at this time, it is difficult to identify the causative agent. However, it has been found that rocuronium is the most common drug associated with perioperative anaphylaxis. We treated 2 cases of patients who were administered sugammadex for anaphylactic symptoms thought to be caused by rocuronium, after which the anaphylactic symptoms disappeared. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
12
0
3
Order By: Relevance
“…The incidence of thyroid diseases is increasing, and surgery is the most common treatment (22)(23)(24). In case of recurrent laryngeal nerve injury, should be done immediately.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of thyroid diseases is increasing, and surgery is the most common treatment (22)(23)(24). In case of recurrent laryngeal nerve injury, should be done immediately.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hydrophobic molecules formed by gamma-cyclodextrin may penetrate body tissues may cause the release of active molecules. Anaphylaxis reactions with sugammadex-rocuronium complex [ 4 , 21 , 22 ] as well as anaphylaxis reactions with rocuronium [ 23 ] are available in the literature, which leads to confusion as to which is the real trigger in anaphylaxis. In the literature, the anaphylaxis reaction associated with sugammadex is not IgE/IgG-mediated [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on this subject includes case reports involving a single patient, case series of 2–3 patients where sugammadex was successful, a few case reports where sugammadex was not successful, and a larger retrospective study involving cases reported to the Western Australian Anesthetic Drug Reaction clinic (see below). The various anecdotal reports, the first of which was published in 2011, outlining the potential successful use of sugammadex in ameliorating or reversing the clinical signs and symptoms following an allergic reaction to rocuronium, are summarized in Table 1 9–24 . These reports include a total of 21 adult patients in whom sugammadex was administered following a suspected allergic reaction to rocuronium.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Postoperative support for the diagnosis of an allergic reaction to rocuronium was not obtained in all patients, but in several included an elevated serum tryptase or histamine level, immunoassays identifying IgE antibody to rocuronium basophil activation in response to rocuronium, or positive intradermal skin testing. One interesting report noted positive skin testing to rocuronium and negative skin testing to sugammadex and the rocuronium‐sugammadex complex 21 …”
Section: Literature Reviewmentioning
confidence: 99%